Risk for and consequences of endometriosis: A critical epidemiologic review - Shafrir, AL; Farland, LV; Shah, DK; Harris, HR; Kvaskoff, M; Zondervan, KT; Missmer, SA (Elsevier, 2018)
Endometriosis affects approximately 10% of women of reproductive age. Characteristics robustly associated with a greater risk for endometriosis include early age at menarche, short menstrual cycle length, and lean body size, whereas greater parity has been associated with a lower risk. Relationships with other potential characteristics including physical activity, dietary factors, and lactation have been less consistent, partially because of the need for rigorous data collection and a longitudinal study design. Critical methodologic complexities include the need for a clear case definition; valid selection of comparison/control groups; and consideration of diagnostic bias and reverse causation when exploring demographic characteristics, medical history, and lifestyle factors. Reviewers and editors must demand a detailed description of rigorous methods to facilitate comparison and replication to advance our understanding of endometriosis.